Textual coherence in Divan Yahya bin Hakam al-Ghazal (d .: 250 A.H) - Karima Abed Jumaa ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
This research was intended to study textual coherence in the poet of the Andalusian poet (Yahya bin Hakam al-Ghazal: T: 250 AH), through two main axes: The first axis: grammatical coherence, in which the techniques of referral, conjunctions, and deletions were studied. The second axis: vocal coherence, in which my techniques were studied: external music from: weighing, rhyme, and internal music from: dashing, vocal repetition, and inclusion.